A Study of the Needs for opening Physical Education Course of Undergraduate Savannakhet University Lao People's Democratic Republic. - KEOMANIVONG, LATDAVONE; Runcharoen, Thacha (Journal for Developing the Social and Community, 2023)
The objectives of this study were to 1) investigate the necessity of a physical education course to be opened and what course Savannakhet University offers for a bachelor's degree in Lao People's Democratic Republic .There were four sample groups in this study comprised students, instructors in the Physical Education Department, and school administrators in the city of Kraisorn Phrom Viharn Savannakhet Sub-District, four schools, via stratified random selection from all schools. It included 304 people, including 280 students, 12 physical education instructors, and 12 school officials. The model of survey research was employed as an approachhow physical training, Savannakhet University offers a bachelor's degree. An analysis of quantitative data ,the data was evaluated using the mean (x), standard deviation (SD), percentage (percent), and qualitative data,by analyzing the context. The result of this study found that Views on the launch of the Bachelor of Physical Education Program at Savannakhet University were found to be mixed. There were 263 people who agreed with the program, accounting for 85.51 percent of the total, and 41 people who opposed it, accounting for 13.49 percent. Physical education courses of Lao People's Democratic Republic had the most reasonable tuition cost (x = 4.94, SD = 0.24) and the need for academic programs at the highest level (x = 4.51, SD = 0.49). The least amount of physical education was that individual sports instruction should be prioritized above team sports teaching (x = 3.76, SD = 0.68).